Non-tailing treatment method for metal mine flotation tailings

By using a mixture of oxylic acid and 2-hydroxypropane-1,2,3-tricarboxylic acid as a quartz feldspar separation regulator, combined with weak magnetic separation and multiple crude selection techniques, the flotation tailings reservoir in metal mines was solved. The problem of existing and environmental pollution has achieved efficient resource utilization and zero emissions of tailings.

CN119456186APending Publication Date: 2025-02-18XIAMEN ZIJIN MINING&METALLURGY TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411591976.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The storage of flotation tailings in metal mines leads to land and environmental damage, and it is difficult for the existing technology to effectively recover valuable components in tailings, and traditional separation processes such as hydrofluoric acid method have safety and environmental risks.

Method used

The mixture of oxylic acid and 2-hydroxypropane-1,2,3-tricarboxylic acid is used as the quartz feldspar separation regulator, combined with weak magnetic separation, sedimentation and desilting and multiple crude selection to achieve tailings Tailless processing and resource utilization.

Benefits of technology

It effectively reduces the number of selected operation segments, improves product grade and recovery rate, reduces the types and usage of drugs, improves safety and environmental friendliness, and realizes zero emissions and resource utilization of tailings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005125827780000011
    Figure HDA0005125827780000011
Patent Text Reader

Abstract

The invention discloses a tailing-free treatment method for flotation tailings of a metal mine, which comprises the following steps: adding oxalic acid into ore pulp of the flotation tailings of the metal mine to adjust the pH value of the ore pulp, and then adding butyl xanthate and terpenic oil for sulfur roughing; performing blank concentration on a foam product obtained by sulfur roughing for three times to obtain sulfur concentrate; the method comprises the following steps: performing low-intensity magnetic separation on sulfur separation tailings obtained by sulfur roughing, performing sedimentation desliming on the tailings obtained by low-intensity magnetic separation to obtain micron-sized fine silt and a crude product, performing roughing on the crude product for five times, adding an adjusting agent of oxalic acid and 2-hydroxypropane-1, 2, 3-tricarboxylic acid combination, lauryl amine and sodium oleate in each time of roughing, blank concentration is conducted on a foam product 1 obtained through first-time roughing to obtain feldspar concentrate 1, foam products and micron-sized fine silt obtained through subsequent roughing are filtered and dried to obtain feldspar concentrate 2, and after fifth-time roughing is finished, ore pulp is filtered and dried to obtain quartz concentrate. The problem of land and environment damage caused by tailing stockpiling can be solved, and tailing resource utilization is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of mineral processing and separation technology, and in particular to a method for treating metal mine flotation tailings without tailings. Background Art

[0002] The flotation tailings of metal mines have the following characteristics: 1) The particle size composition of flotation tailings is generally related to the grinding fineness, and most of the tailings have a particle size of -0.074mm, accounting for 60%-90%; 2) Metal mine flotation tailings generally contain a certain amount of pyrite in varying amounts; 3) The composition of metal mine tailings is complex, and non-metallic minerals generally contain several or dozens of types of mica, quartz, feldspar, chlorite, kaolin, talc, serpentine, etc.

[0003] At present, the flotation tailings of metal mines are generally pumped to the tailings pond for storage after being thickened, and are rarely recycled comprehensively. As a large amount of waste, the accumulation of metal mine tailings not only occupies land resources, but also causes ecological damage. It is particularly important to comprehensively recycle the valuable components in the tailings and realize the reduction, resource utilization and tailing-free utilization of mine tailings.

[0004] Metal mine tailings with albite, potassium feldspar and quartz as the main components are more common. The commonly used and effective separation process for quartz feldspar is the hydrofluoric acid method. In this method, the general amount of hydrofluoric acid used is 3-4kg / t. The amount of hydrofluoric acid used is large, the price is high, and it is harmful to the human body and the environment. With the increasing requirements for occupational safety and environmental protection, industrial applications are rare. The fluorine-free method is difficult to effectively sort mine tailings to obtain qualified non-metallic products. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention aims to provide a method for tailing-free treatment of metal mine flotation tailings. By adopting mineral processing technology, zero discharge of tailings can be achieved, the land and environmental damage caused by tailings storage can be solved, and the resource utilization of tailings can be realized.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A method for treating metal mine flotation tailings without tailings comprises the following steps:

[0008] S1, mixing oxalic acid and 2-hydroxypropane-1,2,3-tricarboxylic acid in a mass ratio of 1:1-2:1, and using the obtained mixture as a quartz feldspar separation regulator;

[0009] S2. Add oxalic acid to the flotation tailings slurry of the metal mine to adjust the pH of the slurry, then add butyl xanthate and pine oil, stir, and perform sulfur roughing; the tailings obtained from the sulfur roughing are sulfur tailings; the foam product obtained from the sulfur roughing is subjected to three blank concentrations and the final foam product obtained is sulfur concentrate;

[0010] S3, performing weak magnetic separation on the sulfur-selected tailings obtained in step S2 to obtain magnetic iron minerals in the sulfur-selected tailings and steel ball debris from metal mine grinding losses, i.e., strongly magnetic iron-containing minerals;

[0011] S4, the tailings obtained after weak magnetic separation in step S3 are subjected to sedimentation and desliming to obtain micron-sized fine mud and coarse product, the coarse product is transferred to step S5 for treatment, and the micron-sized fine mud is transferred to step S12 for treatment;

[0012] S5, the crude product obtained in step S4 is configured into slurry, and the adjusting agent obtained in step S1 is added to adjust the pH value of the slurry, and then dodecylamine and sodium oleate are added, stirred, and the first roughing is performed to separate and obtain foam product 1, and the foam product 1 is transferred to step S10 for treatment;

[0013] S6, continue to add the adjusting agent obtained in step S1 to the slurry after the foam product 1 is separated in step S5 to adjust the pH of the slurry, then add dodecylamine and sodium oleate, stir, and perform a second roughing to separate and obtain the foam product 2, and the foam product 2 is transferred to step S12 for treatment;

[0014] S7, concentrating and dehydrating the pulp after separating the foam product 2 in step S6, then adding the adjusting agent obtained in step S1 to adjust the pH of the pulp, then adding dodecylamine and sodium oleate, stirring, and performing a third roughing to separate and obtain the foam product 3, and the foam product 3 is transferred to step S12 for treatment;

[0015] S8, adding the adjusting agent obtained in step S1 to the slurry after separating the foam product 3 in step S7 to adjust the pH of the slurry, then adding dodecylamine and sodium oleate, stirring, and performing the fourth roughing to separate the foam product 4, and the foam product 4 is transferred to step S12 for treatment;

[0016] S9, adding the adjusting agent obtained in step S1 to the slurry after separating the foam product 4 in step S8 to adjust the pH of the slurry, then adding dodecylamine and sodium oleate, stirring, and performing the fifth roughing to obtain the foam product 5, and the foam product 5 is transferred to step S12 for treatment;

[0017] S10, performing blank concentration on the foam product 1 obtained in step S5, and then filtering and drying the obtained foam product to obtain feldspar concentrate 1;

[0018] S11, filtering and drying the slurry after separating the foam product 5 in step S9 to obtain quartz concentrate;

[0019] S12. Combine the slurry remaining after the foam product is separated by blank selection in step S10, the foam product 2, foam product 3, foam product 4, foam product 5 obtained in steps S6-S9 and the micron-level fine mud obtained in step S4, filter and dry to obtain feldspar concentrate 2.

[0020] Further, in step S2, the fineness of the metal mine flotation tailings slurry is -74μm particle size accounts for 60%-90%, and the mass fraction concentration of the slurry is 25%-40%; oxalic acid is added to the metal mine flotation tailings slurry to adjust the slurry pH to be stable at 5-6.

[0021] Furthermore, in step S2, based on the dry weight of the original ore, the amount of butyl xanthate used is 100-150 g / t, and the amount of pine oil used is 30-50 g / t; and the stirring time is 2 minutes.

[0022] Furthermore, in step S3, the magnetic field strength of the weak magnetic separation is 1000-2000oe.

[0023] Furthermore, in step S5, the mass fraction concentration of the slurry is 20%-40%.

[0024] Furthermore, in step S5, a regulator is added to adjust the pH of the slurry to be stable at 2-2.5; based on the dry weight of the original ore, the amount of dodecylamine is 300-700 g / t, and the amount of sodium oleate is 600-1400 g / t; and the stirring time is 2 minutes.

[0025] Furthermore, in step S6, a regulator is added to adjust the pH of the slurry to be stable at 2-2.5; based on the dry weight of the original ore, the amount of dodecylamine is 150-350 g / t, and the amount of sodium oleate is 300-700 g / t; and the stirring time is 2 minutes.

[0026] Further, in step S7, the mass fraction concentration of the concentrated slurry is 20%-40%; an adjusting agent is added to adjust the pH of the slurry to be stable at 2-2.5; based on the dry weight of the original ore, the amount of dodecylamine is 100-200 g / t, and the amount of sodium oleate is 200-400 g / t; and the stirring time is 2 minutes.

[0027] Furthermore, in step S8, a regulator is added to adjust the pH of the slurry to be stable at 2-2.5; based on the dry weight of the original ore, the amount of dodecylamine is 100-200 g / t, and the amount of sodium oleate is 200-400 g / t; and the stirring time is 2 minutes.

[0028] Furthermore, in step S9, a regulator is added to adjust the pH of the slurry to be stable at 2-2.5; based on the dry weight of the original ore, the amount of dodecylamine is 100-200 g / t, and the amount of sodium oleate is 200-400 g / t; and the stirring time is 2 minutes.

[0029] The beneficial effects of the present invention are:

[0030] 1. The present invention uses oxalic acid as a pH adjuster for flotation of pyrite minerals. Compared with sulfuric acid, the transportation process is safer and more reliable when the price and test indicators are comparable. Compared with copper sulfate, oxalic acid is cheap. When the recovery rate of oxalic acid is comparable, the yield of coarse concentrate is lower and the grade is higher, which can effectively reduce the number of selection operation stages. At the same time, copper sulfate as an activator will introduce copper ions, which can easily cause non-selective activation during quartz feldspar sorting, reduce the difference in floatability of feldspar and quartz, and increase the difficulty of separation. Oxalic acid is also used in the quartz feldspar separation adjuster in the present invention, which can reduce the types of reagents.

[0031] 2. The steel ball loss in the grinding process is related to the ore hardness, grinding fineness, grinding stage number, etc. The grinding steel loss is usually greater than 2.5kg / t of original ore. The weak magnetic separation used in the present invention can effectively recover the primary strong magnetic minerals in the tailings and the secondary steel ball loss generated in the grinding process, while reducing the iron content to improve the grade of quartz feldspar, and recovering the primary and secondary strong magnetic iron minerals.

[0032] 3. Quartz feldspar segmented flotation separation with chemical addition is performed without sedimentation and desludging. The grade of the feldspar concentrate in the first roughing is lower than that in the second roughing, and the dosage of chemical is large, resulting in poor sorting effect. The main reason is the influence of easy-to-mudify fine-grained minerals. The presence of fine-grained easy-to-mudify minerals not only consumes a large amount of collectors, but also causes high viscosity of the slurry and non-selective agglomeration, resulting in poor sorting accuracy and low grade recovery rate. Fine mud is generally composed of minerals with high potassium and sodium contents such as mica and feldspar. The present invention performs sedimentation and desludging in advance to obtain fine-grained fine mud with high potassium and sodium contents, which is feasible for subsequent incorporation into feldspar concentrate.

[0033] 4. The present invention uses a mixture of oxalic acid and 2-hydroxypropane-1,2,3-tricarboxylic acid in a ratio of 1:1-2:1 as a pH adjuster and activator for feldspar quartz. When the quartz is at the zero charge point, the surface of the feldspar is negatively charged, and the amine cationic collector is more easily adsorbed on the surface of the feldspar. The anionic collectors such as sodium oleate cooperate with the amine cationic collectors to more easily separate the quartz and feldspar. At the same time, since the mixed adjuster has different activation degrees for quartz and feldspar as an activator, its activation ability for feldspar is much higher than that for quartz. The addition of the mixed adjuster can significantly increase the floating difference of feldspar and quartz. It replaces sulfuric acid as a pH adjuster, which has more advantages in terms of safe production. Oxalic acid and 2-hydroxypropane-1,2,3-tricarboxylic acid have favorable effects on the separation of feldspar and quartz. After mixing, they can be used as an activator and pH adjuster to produce a synergistic effect. Under the premise of the same dosage, the separation effect is more significant than that of a single use. The present invention adopts the mixed adjusting agent to replace hydrofluoric acid as the feldspar activating agent, and the flotation separation index is equivalent, but the mixed adjusting agent has more advantages in occupational health, technical economy and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 Flow chart of the method of embodiment 1 of the present invention. DETAILED DESCRIPTION

[0035] The present invention will be further described below in conjunction with the accompanying drawings. It should be noted that this embodiment is based on the technical solution and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to this embodiment.

[0036] Example 1

[0037] This embodiment provides a method for treating metal mine flotation tailings without tailings. The metal mine flotation tailings are molybdenum tailings. The molybdenum tailings have a fineness of -0.074mm and a particle size of 70%. The main mineral composition and content are: quartz 50.45%, potassium feldspar 29.81%, sodium feldspar 18.23%, pyrite 0.52%, and magnetite 0.5%. The loss of steel balls in the mine grinding is 2.5kg / t of the original ore, that is, the magnetic iron content in the tailings will increase by 0.2%-0.24% due to the loss of steel balls. Figure 1 As shown, the method of this embodiment includes the following steps:

[0038] S1. Oxalic acid and 2-hydroxypropane-1,2,3-tricarboxylic acid are mixed in a mass ratio of 1:1, and the obtained mixture is used as a quartz feldspar separation regulator.

[0039] S2. Based on the dry weight of each ton of original ore, 500 g / t of oxalic acid is added to the metal mine flotation tailings slurry with a mass fraction concentration of 30% to adjust the slurry pH to 5.8, and then 100 g / t of butyl xanthate and 30 g / t of pine oil are added, and the mixture is stirred for 2 minutes to perform sulfur roughing. The tailings obtained from the sulfur roughing are sulfur tailings. The foam product obtained from the sulfur roughing is subjected to three blank selections and the final foam product is sulfur concentrate. The middlings obtained from each blank selection are returned to the previous operation in sequence, and the foam product obtained enters the next blank selection.

[0040] S3. Add water to the sulfur-selected tailings obtained in step S2 to adjust the mass concentration to 20%, and then use a magnetic drum to perform weak magnetic separation with a magnetic field strength of 1500oe to obtain strongly magnetic iron-containing minerals, which include magnetic iron minerals in the sulfur-selected tailings and steel ball fragments from grinding losses in metal mines.

[0041] S4, the tailings obtained after weak magnetic separation in step S3 are subjected to sedimentation and desliming to obtain micron-level fine mud of -10 μm and coarse product of +10 μm, the coarse product is transferred to step S5 for treatment, and the micron-level fine mud is transferred to step S12 for treatment;

[0042] S5. The +10 μm crude product obtained in step S4 is prepared into a pulp with a mass concentration of 40%. Based on the dry weight of the original ore, 3000 g / t of the adjusting agent obtained in step S1 is added to adjust the pulp pH to 2.2, and then 300 g / t of dodecylamine and 600 g / t of sodium oleate are added. The mixture is stirred for 2 minutes to perform the first roughing, and the foam product 1 is separated and obtained. The foam product 1 is transferred to step S10 for treatment;

[0043] S6, based on the dry weight of the original ore per ton, continue to add 500 g / t of the adjusting agent obtained in step S1 to the slurry after the foam product 1 is separated in step S5 to adjust the slurry pH to 2.3, then add 150 g / t of dodecylamine and 300 g / t of sodium oleate, stir for 2 minutes, perform a second roughing, separate and obtain the foam product 2, and transfer the foam product 2 to step S12 for treatment;

[0044] S7, concentrating and dehydrating the pulp after separating the foam product 2 in step S6, the mass concentration of the concentrated pulp is 40%, then adding 100 g / t of the adjusting agent obtained in step S1 to adjust the pulp pH to 2.4 based on the dry weight of the original ore per ton, then adding 100 g / t of dodecylamine and 200 g / t of sodium oleate, stirring for 2 minutes, and performing the third roughing to separate and obtain the foam product 3, and the foam product 3 is transferred to step S12 for treatment;

[0045] S8, based on the dry weight of the original ore per ton, add 50 g / t of the adjusting agent obtained in step S1 to the slurry after separating the foam product 3 in step S7 to adjust the slurry pH to 2.3, then add 100 g / t of dodecylamine and 200 g / t of sodium oleate, stir for 2 minutes, perform the fourth roughing, separate and obtain the foam product 4, and transfer the foam product 4 to step S12 for treatment;

[0046] S9, based on the dry weight of the original ore per ton, add 50 g / t of the adjusting agent obtained in step S1 to the slurry after separating the foam product 4 in step S8 to adjust the slurry pH to 2.2, then add 100 g / t of dodecylamine and 200 g / t of sodium oleate, stir for 2 minutes, and perform the fifth roughing to obtain the foam product 5, which is transferred to step S12 for treatment;

[0047] S10, performing blank concentration on the foam product 1 obtained in step S5, and then filtering and drying the obtained foam product to obtain feldspar concentrate 1;

[0048] S11, filtering and drying the slurry after separating the foam product 5 in step S9 to obtain quartz concentrate;

[0049] S12. Combine the slurry remaining after the foam product is separated by blank selection in step S10, the foam product 2, foam product 3, foam product 4, foam product 5 obtained in steps S6-S9 and the micron-level fine mud obtained in step S4, filter and dry to obtain feldspar concentrate 2.

[0050] According to the test, the molybdenum tailings contain 0.29% sulfur, 0.8% iron, 80.4% silicon dioxide and 7.08% potassium oxide + sodium oxide. The sulfur grade of the pyrite obtained after treatment by the method of this embodiment is 45.82%, the yield is 0.51%, and the recovery rate is 84%; the iron grade of the strong magnetic iron mineral is 60.23%, the recovery rate is 73.24%, and the yield is 0.52%; the K2O+Na2O grade of feldspar concentrate 1 is 12.53%, and the feldspar concentrate yield is 19.35%; the K2O+Na2O grade of feldspar concentrate 2 is 10.48%, and the feldspar concentrate yield is 35.21% (wherein the -10μm fine mud yield is 5.29%, and the K2O+Na2O grade is 9.53%;); the SiO2 grade of the quartz concentrate is 93.18%, the K2O+Na2O grade is 2.17%, and the yield is 44.41%.

[0051] Comparative Example 1

[0052] Copper sulfate was used as a sulfur activator, butyl xanthate was used as a pyrite collector, and pine oil was used as a foaming agent to perform pyrite roughing on the molybdenum tailings described in Example 1. The obtained pyrite roughing tailings were not subjected to sedimentation and desludging. Sulfuric acid was used as a pH adjuster, sodium hexametaphosphate was used as a dispersant, and octadecylamine + sodium dodecylsulfonate were used as collectors to separate feldspar and quartz from the pyrite roughing tailings. The yield of pyrite rough concentrate obtained by pyrite roughing was as high as 5%, and the sulfur grade was 5.23%. The feldspar concentrate K2O+Na2O grade obtained by feldspar and quartz separation was 8.52%, the yield was 31.05%, and the SiO2 grade of the quartz concentrate at the bottom of the trough was 83.12%. Feldspar and quartz were not effectively separated, and qualified feldspar and quartz concentrates could not be obtained.

[0053] Comparative Example 2

[0054] The weak magnetic separation tailings obtained in step S3 of Example 1 were subjected to flotation desliming using sulfuric acid as a pH adjuster and dodecylamine as a collector. The tailings after flotation desliming were then separated from feldspar quartz using oxalic acid and 2-hydroxypropane-1,2,3-tricarboxylic acid as adjusters, dodecylamine and sodium oleate as collectors. The obtained flotation desliming yield was 20%, the K2O+Na2O grade was 7.59%, the K2O+Na2O grade of the feldspar concentrate obtained by flotation was 10.23%, and the SiO2 grade of the quartz concentrate was 89.01%. Only the feldspar concentrate had a qualified grade, the flotation desliming grade was low, and the yield was high. It could not be incorporated into the feldspar concentrate and could only be stored separately.

[0055] Comparative Example 3

[0056] The +10μm crude product obtained in step S4 of Example 1 is separated from feldspar and quartz according to steps S5-S12 using oxalic acid and 2-hydroxypropane-1,2,3-tricarboxylic acid as adjusting agents, dodecylamine and sodium oleate as collecting agents. The main difference is that the fifth roughing in Example 1 is changed to scavenging (the dosage of reagents is the same), the concentrates obtained from the first four roughings are combined for two blank concentrations, and the concentrated ore and the scavenged ore are returned in sequence. The K2O+Na2O grade of the obtained feldspar concentrate is 11.23%, and the operating yield of the feldspar concentrate is 46.73%; the SiO2 grade of the quartz concentrate is 88.23%, the K2O+Na2O grade is 3.44%, and the operating yield is 53.27%. The process structure of this comparative example is more complicated than that of Example 1, more flotation equipment is required, the operation controllability is poor, and the quartz concentrate does not meet the requirements of qualified products.

[0057] Example 2

[0058] This embodiment provides a method for treating metal mine flotation tailings without tailings. The metal mine flotation tailings are copper tailings. The copper tailings have a fineness of -0.074 mm and a particle size of 80%. The main mineral composition and content are: quartz 37.34%, potassium feldspar 36.21%, albite 14.23%, muscovite 1.24%, pyrite 1.12%, pyrrhotite 0.55%, magnetite 3.12%, and copper sulfide ores such as chalcopyrite and chalcocite. The loss of grinding steel balls in the mine is 2.3 kg / t of original ore. The method of this embodiment includes the following steps:

[0059] S1. Oxalic acid and 2-hydroxypropane-1,2,3-tricarboxylic acid are mixed in a mass ratio of 2:1, and the obtained mixture is used as a quartz feldspar separation regulator.

[0060] S2. Based on the dry weight of each ton of original ore, 500 g / t of oxalic acid is added to the metal mine flotation tailings slurry with a mass fraction concentration of 30% to adjust the slurry pH to 6, and then 150 g / t of butyl xanthate and 50 g / t of pine oil are added, and stirred for 2 minutes to carry out sulfur roughing; the tailings obtained from the sulfur roughing are sulfur tailings; the foam product obtained from the sulfur roughing is subjected to a blank selection and the final foam product obtained is sulfur concentrate; the middlings obtained from the blank selection are sequentially returned to the previous operation, and the obtained foam products enter the next blank selection.

[0061] S3. Add water to the sulfur-selected tailings obtained in step S2 to adjust the mass concentration to 18%, and then use a magnetic drum to perform weak magnetic separation with a magnetic field strength of 2000oe to obtain strongly magnetic iron-containing minerals, which include magnetic iron minerals in the sulfur-selected tailings and steel ball fragments from grinding losses in metal mines.

[0062] S4, the tailings obtained after weak magnetic separation in step S3 are subjected to sedimentation and desliming to obtain micron-level fine mud of -10 μm and coarse product of +10 μm, the coarse product is transferred to step S5 for treatment, and the micron-level fine mud is transferred to step S12 for treatment;

[0063] S5. The +10 μm crude product obtained in step S4 is prepared into a pulp with a mass concentration of 35%. Based on the dry weight of the original ore, 4000 g / t of the adjusting agent obtained in step S1 is added to adjust the pulp pH to 2.0, and then 700 g / t of dodecylamine and 1400 g / t of sodium oleate are added, stirred for 2 minutes, and the first roughing is performed to separate and obtain foam product 1, which is transferred to step S10 for treatment;

[0064] S6, based on the dry weight of the original ore per ton, continue to add 400 g / t of the adjusting agent obtained in step S1 to the slurry after the foam product 1 is separated in step S5 to adjust the slurry pH to 2.5, then add 350 g / t of dodecylamine and 700 g / t of sodium oleate, stir for 2 minutes, perform a second roughing, separate and obtain the foam product 2, and transfer the foam product 2 to step S12 for treatment;

[0065] S7, concentrating and dehydrating the pulp after separating the foam product 2 in step S6, the mass concentration of the concentrated pulp is 40%, then adding 80 g / t of the adjusting agent obtained in step S1 to adjust the pulp pH to 2.5 based on the dry weight of the original ore per ton, then adding 200 g / t of dodecylamine and 400 g / t of sodium oleate, stirring for 2 minutes, and performing the third roughing to separate and obtain the foam product 3, and the foam product 3 is transferred to step S12 for treatment;

[0066] S8, based on the dry weight of the original ore per ton, add 80 g / t of the adjusting agent obtained in step S1 to the slurry after separating the foam product 3 in step S7 to adjust the slurry pH to 2.1, then add 200 g / t of dodecylamine and 400 g / t of sodium oleate, stir for 2 minutes, perform the fourth roughing, separate and obtain the foam product 4, and transfer the foam product 4 to step S12 for treatment;

[0067] S9, based on the dry weight of the original ore per ton, add 80 g / t of the adjusting agent obtained in step S1 to the slurry after separating the foam product 4 in step S8 to adjust the slurry pH to 2.0, then add 200 g / t of dodecylamine and 400 g / t of sodium oleate, stir for 2 minutes, and perform the fifth roughing to obtain the foam product 5, which is transferred to step S12 for treatment;

[0068] S10, performing blank concentration on the foam product 1 obtained in step S5, and then filtering and drying the obtained foam product to obtain feldspar concentrate 1;

[0069] S11, filtering and drying the slurry after separating the foam product 5 in step S9 to obtain quartz concentrate;

[0070] S12. Combine the slurry remaining after the foam product is separated by blank selection in step S10, the foam product 2, foam product 3, foam product 4, foam product 5 obtained in steps S6-S9 and the micron-level fine mud obtained in step S4, filter and dry to obtain feldspar concentrate 2.

[0071] According to the test, the copper tailings contain 0.80% sulfur, 3.21% iron, 76.81% silicon dioxide, 6.34% potassium oxide, 1.70% sodium oxide, and 8.07% potassium oxide + sodium oxide. The sulfur grade of the pyrite obtained after treatment by the method of this embodiment is 43.43%, the yield is 1.59%, and the recovery rate is 86.32%; the iron grade of the strong magnetic iron mineral is 60.34%, the recovery rate is 67.74%, and the yield is 3.71%; the K2O+Na2O grade of feldspar concentrate 1 is 13.59%, and the feldspar concentrate yield is 26.71%; the K2O+Na2O grade of feldspar concentrate 2 is 10.22%, and the feldspar concentrate yield is 34.34% (wherein the -10μm fine mud yield is 6.21%, and the K2O+Na2O grade is 9.33%;); the SiO2 grade of the quartz concentrate is 94.11%, the K2O+Na2O grade is 1.93%, and the yield is 35.47%.

[0072] Comparative Example 4

[0073] Copper sulfate is used as a sulfur activator, butyl xanthate is used as a pyrite collector, and pine oil is used as a foaming agent to perform pyrite roughing on the copper tailings described in Example 2. The roughing tailings obtained are not subjected to sedimentation and desludging. Sulfuric acid is used as a pH adjuster, acidic water glass is used as a dispersant, and dodecylamine + sodium sulfate is used as a collector to separate feldspar quartz. The yield of pyrite rough concentrate obtained by pyrite roughing is as high as 10%, the sulfur grade is 7.21%, the selection operation pressure is high, and the cost of flotation reagents is high. The feldspar concentrate K2O+Na2O grade obtained by feldspar quartz separation is 9.21%, the yield is 50.23%, and the SiO2 grade of the quartz concentrate at the bottom of the trough is 83.12%. Feldspar quartz cannot be effectively sorted, and qualified feldspar and quartz concentrates cannot be obtained.

[0074] Comparative Example 5

[0075] The weak magnetic separation tailings obtained in step S3 of Example 2 were subjected to flotation desliming using sulfuric acid as a pH adjuster and dodecylamine as a collector, and then feldspar quartz separation was performed on the tailings after flotation desliming using oxalic acid and 2-hydroxypropane-1,2,3-tricarboxylic acid as adjusters, dodecylamine and sodium oleate as collectors. The flotation desliming yield was 30.34%, the K2O+Na2O grade was 9.21%, the K2O+Na2O grade of the feldspar concentrate obtained by feldspar quartz separation was 10.58%, the yield was 32.12%, and the SiO2 grade of the quartz concentrate was 91.02%. The flotation desliming yield was large, and directly incorporating it into the feldspar concentrate would cause the feldspar concentrate grade to fail to meet the standard.

[0076] Comparative Example 6

[0077] The +10μm crude product obtained in step S4 of Example 2 was separated from feldspar quartz using oxalic acid and 2-hydroxypropane-1,2,3-tricarboxylic acid as regulators, dodecylamine and sodium oleate as collectors. The dosage of reagents in each implementation step was equal to that in Example 1. The main difference was that the fourth and fifth roughings in Example 1 were changed to scavenging 1 and scavenging 2 (the dosage of reagents was the same as that in the fourth and fifth roughings). The concentrates obtained from the first three roughings were combined for two blank concentrations, and the concentrated ore and the scavenged ore were returned in sequence. The K2O+Na2O grade of the obtained feldspar concentrate was 11.15%, and the operating yield of the feldspar concentrate was 55.43%; the SiO2 grade of the quartz concentrate was 92.23%, the K2O+Na2O grade was 4.24%, and the yield was 44.57%. The process structure of this comparative example is more complicated than that of Example 2, more flotation equipment is required, the operation controllability is poor, and the grade of the feldspar concentrate fluctuates greatly.

[0078] For those skilled in the art, various corresponding changes and modifications can be made according to the above technical solutions and concepts, and all of these changes and modifications should be included in the protection scope of the claims of the present invention.

Claims

1. A method for treating metal mine flotation tailings without tailings, characterized in that: The following steps are involved: S1, mixing oxalic acid and 2-hydroxypropane-1,2,3-tricarboxylic acid in a mass ratio of 1:1-2:1, and using the obtained mixture as a quartz feldspar separation regulator; S2. Add oxalic acid to the flotation tailings slurry of the metal mine to adjust the pH of the slurry, then add butyl xanthate and pine oil, stir, and perform sulfur roughing; the tailings obtained from the sulfur roughing are sulfur tailings; the foam product obtained from the sulfur roughing is subjected to three blank concentrations and the final foam product obtained is sulfur concentrate; S3, performing weak magnetic separation on the sulfur-selected tailings obtained in step S2 to obtain magnetic iron minerals in the sulfur-selected tailings and steel ball debris from metal mine grinding losses, i.e., strongly magnetic iron-containing minerals; S4, the tailings obtained after weak magnetic separation in step S3 are subjected to sedimentation and desliming to obtain micron-sized fine mud and coarse product, the coarse product is transferred to step S5 for treatment, and the micron-sized fine mud is transferred to step S12 for treatment; S5, the crude product obtained in step S4 is configured into slurry, and the adjusting agent obtained in step S1 is added to adjust the pH value of the slurry, and then dodecylamine and sodium oleate are added, stirred, and the first roughing is performed to separate and obtain foam product 1, and the foam product 1 is transferred to step S10 for treatment; S6, continue to add the adjusting agent obtained in step S1 to the slurry after the foam product 1 is separated in step S5 to adjust the pH of the slurry, then add dodecylamine and sodium oleate, stir, and perform a second roughing to separate and obtain the foam product 2, and the foam product 2 is transferred to step S12 for treatment; S7, concentrating and dehydrating the pulp after separating the foam product 2 in step S6, then adding the adjusting agent obtained in step S1 to adjust the pH of the pulp, then adding dodecylamine and sodium oleate, stirring, and performing a third roughing to separate and obtain the foam product 3, and the foam product 3 is transferred to step S12 for treatment; S8, adding the adjusting agent obtained in step S1 to the slurry after separating the foam product 3 in step S7 to adjust the pH of the slurry, then adding dodecylamine and sodium oleate, stirring, and performing the fourth roughing to separate the foam product 4, and the foam product 4 is transferred to step S12 for treatment; S9, adding the adjusting agent obtained in step S1 to the slurry after separating the foam product 4 in step S8 to adjust the pH of the slurry, then adding dodecylamine and sodium oleate, stirring, and performing the fifth roughing to obtain the foam product 5, and the foam product 5 is transferred to step S12 for treatment; S10, performing blank concentration on the foam product 1 obtained in step S5, and then filtering and drying the obtained foam product to obtain feldspar concentrate 1; S11, filtering and drying the slurry after separating the foam product 5 in step S9 to obtain quartz concentrate; S12. Combine the slurry remaining after the foam product is separated by blank selection in step S10, the foam product 2, foam product 3, foam product 4, foam product 5 obtained in steps S6-S9 and the micron-level fine mud obtained in step S4, filter and dry to obtain feldspar concentrate 2.

2. The method according to claim 1, characterized in that In step S2, the fineness of the metal mine flotation tailings slurry is -74μm, accounting for 60%-90%, and the mass fraction concentration of the slurry is 25%-40%; oxalic acid is added to the metal mine flotation tailings slurry to adjust the slurry pH to be stable at 5-6.

3. The method according to claim 1, characterized in that: In step S2, based on the dry weight of the original ore, the amount of butyl xanthate used is 100-150 g / t, and the amount of pine oil used is 30-50 g / t; the stirring time is 2 minutes.

4. The method according to claim 1, characterized in that In step S3, the magnetic field strength of weak magnetic separation is 1000-2000oe.

5. The method according to claim 1, characterized in that In step S5, the mass fraction concentration of the slurry is 20%-40%.

6. The method according to claim 1, characterized in that In step S5, a regulator is added to adjust the pH value of the slurry to be stable at 2-2.5; based on the dry weight of the original ore, the amount of dodecylamine is 300-700 g / t, and the amount of sodium oleate is 600-1400 g / t; and the stirring time is 2 minutes.

7. The method according to claim 1, characterized in that In step S6, a regulator is added to adjust the pH of the slurry to be stable at 2-2.5; based on the dry weight of the original ore, the amount of dodecylamine is 150-350 g / t, and the amount of sodium oleate is 300-700 g / t; and the stirring time is 2 minutes.

8. The method according to claim 1, characterized in that: In step S7, the mass fraction concentration of the concentrated slurry is 20%-40%; an adjusting agent is added to adjust the pH of the slurry to be stable at 2-2.5; based on the dry weight of the original ore, the amount of dodecylamine is 100-200 g / t, and the amount of sodium oleate is 200-400 g / t; and the stirring time is 2 minutes.

9. The method according to claim 1, characterized in that: In step S8, a regulator is added to adjust the pH value of the slurry to be stable at 2-2.5; based on the dry weight of the original ore, the amount of dodecylamine is 100-200 g / t, and the amount of sodium oleate is 200-400 g / t; and the stirring time is 2 minutes.

10. The method according to claim 1, characterized in that In step S9, a regulator is added to adjust the pH of the slurry to be stable at 2-2.5; based on the dry weight of the original ore, the amount of dodecylamine is 100-200 g / t, and the amount of sodium oleate is 200-400 g / t; and the stirring time is 2 minutes.

Citation Information

Patent Citations

  • Method for separating potassium feldspar and soda feldspar from potassium-soda feldspar ore

    CN103785524A

  • Method for recycling feldspar from gold flotation tailings through fluoride-free alkali process

    CN105057113A

  • Combined collector for feldspar and quartz flotation separation and application method

    CN107185721A

  • Preparation method of high-purity quartz sand

    CN110665631A

  • Method for separating quartz for refractory material products from lead-zinc sulfide ore tailings

    CN117000417A